Intoxicação por marsdenia megalantha Goyder & Morillo em animais de produção - Geraldo Neto, Severino Antonio (2017)
The genus Marsdenia belongs to the Apocynaceae(Asclepiadoideae)family, are distributed worldwide and although several species of this genus are used in traditional Asian medicine for the treatment of rheumatic pain, inflammation, asthma, syphilis and cancer.Marsdenia megalantha is a rupicolous shrub with succulent roots of the semi-arid region of Brazil, is mentioned by farmers as the cause of intoxication in cattle, goats, sheep, pigs, equines and asinines. The clinical and pathological findings of the experimental administration of M. megalantha to sheep, goats, calf and swine are reported. Were dosed once orally with freshly chopped roots at dose of 25 g wet plant/kg bw; another sheep ad a pig were dosed with 10g wet plant/kg bw. Poisoning occurred in all of the animals except the three goats. Clinical signs of poisoning included tachycardia, opisthotonus, ruminal bloat, dyspnea, nystagmus, mydriasis, ataxia, and recumbence with paddling moviments. Pathological evaluation showed segmental laminar neuronal necrosis and spongiosis in the telencephalic cortex and degeneration of Purkinje cells. The picrate paper procedure detected no cyanide in the plant roots, but the reaction used for nitrate detection gave a strongly positive response. In a second experiment a dose of 10, 25 and 7 g / kg, respectively, was given to a cow, a goat and a sheep with calves of approximately 30 days. Aiming to assess whether the toxic principle, still unknown, passed through the milk and would be intoxicating the lactating animals. The administration lasted 5 days in the cow, 10 days in the sheep and only three days in the goat. And only the goat showed clinical signs of intoxication, no other animals nor their offspring showed any clinical signs. In conclusion, M. megalantha is a plant that produces acute intoxication characterized mainly by nervous disorders, the toxic principle or the toxic principles did not pass through the milk or passed in quantities insufficient to cause intoxication in the young, the pig was the species more sensitive to the goat The most resistant to intoxication, and producers of production animals should offer alternative foods during the dry season and early in the rainy season to avoid the occurrence of intoxication by this plant